Differential miRNA expression of hypoxic MCF7 and PANC-1 cells - Al-Sisan, Sandy M.; Zihlif, Malek A.; Hammad, Hana M. (Frontiers in Endocrinology, 2023)
Background Hypoxia plays a critical role in the tumor microenvironment by affecting cellular proliferation, metabolism, apoptosis, DNA repair, and chemoresistance. Since hypoxia provokes a distinct shift of microRNA, it is important to illustrate the relative contribution of each hypoxamiR to cancer progression. Aims The present study aims to shed light on the hypoxamiRs that are involved in pancreatic and breast cancer progression to highlight novel targets for the development of new therapies. Methods For 20 cycles, MCF7 breast cancer cells and PANC-1 pancreatic cancer cells were subjected to chronic cyclic hypoxia, which consisted of 72 hours of hypoxia followed by 24 hours of reoxygenation. After 10 and 20 cycles of hypoxia, miRNA expression alterations were profiled using RT-PCR array and further analyzed using a visual analytics platform. The MTT cell proliferation assay was used to determine hypoxic cells’ chemoresistance to doxorubicin. Results Under chronic cyclic hypoxia, hypoxic PANC-1 cells have a comparable doubling time with their normoxic counterparts, whereas hypoxic MCF7 cells show a massive increase in doubling time when compared to their normoxic counterparts. Both hypoxic cell lines developed EMT-like phenotypes as well as doxorubicin resistance. According to the findings of miRNet, 6 and 10 miRNAs were shown to play an important role in enriching six hallmarks of pancreatic cancer in the 10th and 20th cycles of hypoxia, respectively, while 7 and 11 miRNAs were shown to play an important role in enriching the four hallmarks of breast cancer in the 10th and 20th cycles of hypoxia, respectively. Conclusions miR-221, miR-21, miR-155, and miR-34 were found to be involved in the potentiation of hypoxic PANC-1 hallmarks at both the 10th and 20th cycles, while miR-93, miR-20a, miR-15, and miR-17 were found to be involved in the potentiation of hypoxic MCF7 hallmarks at both the 10th and 20th cycles. This variation in miRNA expression was also connected to the emergence of an EMT-like phenotype, alterations in proliferation rates, and doxorubicin resistance. The chemosensitivity results revealed that chronic cyclic hypoxia is critical in the formation of chemoresistant phenotypes in pancreatic and breast cancer cells. miR-181a and let-7e expression disparities in PANC1, as well as miR-93, miR-34, and miR-27 expression disparities in MCF7, may be associated with the formation of chemoresistant MCF7 and PANC-1 cells following 20 cycles of chronic cyclic hypoxia. Indeed, further research is needed since the particular mechanisms that govern these processes are unknown.